Temporal and palaeoclimatic context of the evolution of insular woodiness in the Canary Islands. Issue 17 (17th August 2021) - Hooft van Huysduynen, Alexander; Janssens, Steven; Merckx, Vincent; Vos, Rutger; Valente, Luis; Zizka, Alexander; Larter, Maximilian; Karabayir, Betül; Maaskant, Daphne; Witmer, Youri; Fernández‐Palacios, José María; de Nascimento, Lea; et al.
Abstract: Insular woodiness (IW), referring to the evolutionary transition from herbaceousness toward woodiness on islands, has arisen more than 30 times on the Canary Islands (Atlantic Ocean). One of the IW hypotheses suggests that drought has been a major driver of wood formation, but we do not know in which palaeoclimatic conditions the insular woody lineages originated. Therefore, we provided an updated review on the presence of IW on the Canaries, reviewed the palaeoclimate, and estimated the timing of origin of woodiness of 24 insular woody lineages that represent a large majority of the insular woody species diversity on the Canaries. Our single, broad‐scale dating analysis shows that woodiness in 60%–65% of the insular woody lineages studied originated within the last 3.2 Myr, during which Mediterranean seasonality (yearly summer droughts) became established on the Canaries. Consequently, our results are consistent with palaeoclimatic aridification as a potential driver of woodiness in a considerable proportion of the insular woody Canary Island lineages. However, the observed pattern between insular woodiness and palaeodrought during the last couple of million years could potentially have emerged as a result of the typically young age of the native insular flora, characterized by a high turnover. Abstract : We provided an updated review on the presence of insular woodiness on the Canaries, reviewed the palaeoclimate, and estimated the timing of origin of woodiness of 24 insular woody lineages of the Canary Islands (Spain). Our single, broad‐scale molecular dating analysis shows that woodiness in 60%–65% of the insular woody lineages studied originated within the last 3.2 Myr, consistent with palaeoclimatic aridification as a potential driver of woodiness.